THE RELATION BETWEEN HONEY STORAGE AND POLLEN GRAINS AT HONEY BEES WORKERS (Apis Mellifera L) ACTIVITY ON WANDERING AND COLLECTION TO PROVIDE FOOD NECESSARY FOR THE GROWTH AND DEVELOPMENT OF THE COLONY - Mahdi Mohammed Salih Saeed (Mesopotamia Journal of Agriculture)
Effect of storing honey and pollen grains for bees workers on groups of honey bees (strong. medium. weak) show that the best area was for the strong groups and the least for the weak ones. The best periods of storage after collecting honey was on June 25th and for pollen grains on May 15th. for the open broad on May 15th and for the closed broad on May 25th for all the groups. The best wandering for the three groups as related to the collection of pollen grains was for the strong hives and the less for the weak ones. The best periods of wandering was on June 16th and for pollen grains on May 25th for all the groups. Simple correlation (r) results were significantly positive for the correlation of honey. pollen grains. open and closed broad. honey bees wandering and pollen grains at 0.01 probability. The correlation of stored honey area with honey bees wandering was highly significant 92% and also with the stored pollen grains with the honey bees wandering 68% .